Analyzing Dengue Transmission Through a Two-Age-Class Host Population Model - Eminugroho Sari; Dwi Lestari; Nikenasih Binatari; Retno Subekti; Fitriana Saptaningtyas (Department of Mathematics, Universitas Negeri Gorontalo, 2026)
Age is an important risk factor for vector-borne diseases such as dengue. Children are more exposed to mosquito bites than adults due to behavioral and environmental factors. This study extends the classical host-vector modeling framework by incorporating the human population divided into two age classes, i.e, children and adults. The model also introduces additional key biological parameters, such as b, the number of mosquito bites per day; σ, the intrinsic growth rate of the mosquito population; and η, the relative probability that a mosquito bites an adult rather than a child. We derive the basic reproduction number using the next-generation matrix method and analyze the local stability of the disease-free equilibrium. Furthermore, we obtain sufficient conditions for the local asymptotic stability of the endemic equilibrium in a specific case. Sensitivity analysis is discussed to identify parameters that have the most influence. The numerical simulations are provided to support the theoretical results.